Effect of phenotypic switching on the susceptibility of candida krusei towards amphotericin B, nystatin and piper betle aqueous extract - Arzmi, Mohd Hafiz (IIUM Press, 2020)
Candida krusei (C. krusei) is associated with oral candidiasis, particularly in immune-compromised patients. The objective of the study was to determine the effect of phenotypic switching to the susceptibility of C. krusei towards amphotericin B, nystatin and aqueous extract of Piper betle (P. betle). To induce phenotypic switching, C. krusei was inoculated in yeast extract peptone dextrose (YEPD) broth supplemented with 5 mg mL-1 phloxine B and incubated for five hours at 25 C. Later, 100 μL of the suspension was inoculated on YEPD agar supplemented with 5 mg mL-1 phloxine B and incubated for five days at 25 C. Disc diffusion and minimum inhibitory concentration (MIC) assays were conducted to determine the susceptibility of C. krusei. The results showed that all C. krusei switched generations were susceptible towards amphotericin B and nystatin with the 3rd and 4th generations significantly more susceptible than the un-switched, respectively (P<0.05). All C. krusei switched generations were also observed to be susceptible towards the aqueous extract of P. betle. The MIC of amphotericin B, nystatin and P. betle were determined at 10 μg mL-1, 10 μg mL-1 and 12.5 mg mL-1, respectively for all generations of C. krusei. In conclusion, the susceptibility of C. krusei was phenotypically switched generation dependent towards amphotericin B, nystatin, and Piper betle aqueous extract.